SENSORY, PHYSICAL AND CHEMICAL CHARACTERISTICS OF MEAT FROM FREE-RANGE REARED SWALLOW-BELLY MANGULICA PIGS - Vladimir M. Tomović; Božidar A. Žlender; Marija R. Jokanović; Mila M. Tomović; Branislav V. Šojić; Snežana B. Škaljac; Žarko S. Kevrešan; Tatjana A. Tasić; Predrag M. Ikonić; Milena M. Šošo (Journal of Animal and Plant Sciences, 2014)
Sensory (colour and marbling score), physical (pH, water-holding capacity and L*a*b* values) and chemical (moisture, protein, total fat, total ash, potassium - K, phosphorus - P, sodium - Na, magnesium - Mg, calcium - Ca, zinc - Zn, iron - Fe, copper - Cu and manganese - Mn) characteristics were determined in four (M. psoas major, M. semimembranosus, M. longissimus dorsi, and M. triceps brachii) muscles belonging to free-range reared Swallow-belly Mangulica pigs. Muscle had no significant influence (P>0.05) on pH30min, water-holding capacity, b* value, protein, total ash and K concentration. M. longissimus dorsi had significantly (P<0.05) the lightest colour (sensory score, L* value, a* value), the lowest moisture concentration, the highest fat concentration and sensory marbling score. The pH24h and Zn concentration were the highest in M. triceps brachii. The highest concentration of K, Mg, Fe, Cu and Mn was found in the M. psoas major, with significant difference for Fe (P<0.05). In the M. semimembranosus significantly the highest (P<0.05) concentration of Na and Ca, and the highest concentration of P were found. Compared to modern pigs, pork from 150 kg live weight, at the age of about 20 months, Swallow-belly Mangulica pigs contained more fat and was darker, while compared to autochthonous pigs determined pork quality were in the characteristic ranges.
Keywords: Pigs; Swallow-Belly Mangulica; Meat; Sensory characteristics; Physical characteristics; Chemical characteristics